2020
DOI: 10.20853/34-2-4044
|View full text |Cite
|
Sign up to set email alerts
|

Tracking five years of teacher education enrolment at a South African university: Implications for teacher education

Abstract: The faculty in which we are based offers two initial teacher training programmes: the Postgraduate Certificate in Education (PGCE); and the four-year BEd qualification-allowing students to pursue a specialisation in either the foundation or intermediate phase. Compared to other faculties, the Faculty of Education occupies the somewhat precarious label of being one of the "most transformed" faculty in the university. In other words, given the historical privilege of the university, the Faculty of Education is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…Regrettably, Gilakjani, Leong and Ismail (2013) lament that a critical analysis of the nature and type of teaching to which students are exposed reveals that very little has changed from the highly lecturercentred learning environments where the lecturer merely passes information to students and gives orders. Davids and Waghid (2020) caution that while academic performance remains at the core of success, access and retention in higher education, students experience the most severe sense of exclusion, alienation and displacement in the learning environment. The reasons advanced by Davids and Waghid (2020) for this are that the students are not able to navigate through the demands and expectations of the learning environment and that they are never heard or seen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regrettably, Gilakjani, Leong and Ismail (2013) lament that a critical analysis of the nature and type of teaching to which students are exposed reveals that very little has changed from the highly lecturercentred learning environments where the lecturer merely passes information to students and gives orders. Davids and Waghid (2020) caution that while academic performance remains at the core of success, access and retention in higher education, students experience the most severe sense of exclusion, alienation and displacement in the learning environment. The reasons advanced by Davids and Waghid (2020) for this are that the students are not able to navigate through the demands and expectations of the learning environment and that they are never heard or seen.…”
Section: Introductionmentioning
confidence: 99%
“…Davids and Waghid (2020) caution that while academic performance remains at the core of success, access and retention in higher education, students experience the most severe sense of exclusion, alienation and displacement in the learning environment. The reasons advanced by Davids and Waghid (2020) for this are that the students are not able to navigate through the demands and expectations of the learning environment and that they are never heard or seen. Although the dominant discourses of teaching and learning and the students' learning experiences in higher education tend to differ significantly among institutions, socially, geographically, economically and politically they are defined by specific discourses which form part of the pedagogical ethos and teaching culture in the learning environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the participants (n = 40; 88.9%) were aged between 21 and 32 and the majority of participants were African (n = 22; 48.9%). These findings were not surprising as Davids and Waghid (2020) indicated that the majority of those enrolled for PGCE qualifications in South Africa are females, those of a younger age and black individuals.…”
Section: Methodsmentioning
confidence: 83%
“…Higher education has traditionally been considered as a "public good" (Davids and Waghid 2020;Marshall 2016). However, the contemporary world is also witnessing an increasing trend towards privatisation of higher education.…”
Section: Contributions Of the Che Conference To The Discoursementioning
confidence: 99%